Colloid and interface chemistry for water quality control - Chang, Qing (Academic Press, 2016)
Colloid and Interface Chemistry for Water Quality Control provides basic but essential knowledge of colloid and interface science for water and wastewater treatment. Divided into two sections, chapters 1 to 8 presents colloid chemistry including simple history and basic concepts, diffusion and Brown Motion, sedimentation, osmotic pressure, optical properties, rheology properties, electric properties, emulsion, foam and gel, and so on; chapters 9 to provides interface chemistry theories including the surface of liquid, the surface of solution, and the surface of solid. This valuable book is the only one that presents colloid and interface chemistry from the water quality control perspective. This book was written for graduate students in the area of water treatment and environmental engineering, and it could be used as the reference for researchers and engineers in the same area.--Provided by publisher.